Ändringar i vapenlagen för att motverka vapenvåld: kunskapen bakom och effekterna av lagförslagen - Helén,Josefin; Karlsson,Emma (2018)
This bachelor thesis examines the Swedish arms law and its development, by investigating its changes since it first was founded. The law applicable today was founded in 1996. It has been changed 22 times since then, where 13 of these changes had the purpose to prevent crimes where weapons are involved. Furthermore, this bachelor thesis also examines the knowledge behind the political arguments stated in government bills that argued for these changes. This was done by examining the pro and contra arguments in legislative proposals and comparing these with previous research on this matter. Consequently, knowledge could be acquired about how sustainable these arguments are. The theory about parallel norm creating process was used as a theoretical framework for understanding these legislative changes. After the argumentations behind the legislative proposals had been analyzed and valued, the results were compared with statistics from Brottsförebyggande rådet concerning different types of crimes with weapons involved. The statistics acts as an indicator for how well these changes in the Swedish arms law actually have prevented the crimes that they aimed to prevent. The result showed that the majority of the political arguments were not sustainable in relation to previous research and therefore, that the knowledge behind these changes is incomplete. Interestingly, the statistics show that the occurrence of these crimes has increased after the majority of the investigated legislative changes. Thus, it is possible to question the knowledge behind these legislative proposals in a severe manner.
Keywords: brottsbekämpning; lagändringar; politikers kunskap; vapenlagen; vapenvåld